ILLEGAL EVIDENCE IN CRIMINAL PROCEDURE IN CASE-LAW OF SUPREME COURT OF CASSATION IN 2019 AND 2020 - Pisarić, Milana (Glasnik Advokatske komore Vojvodine, 2021)
The Code of Criminal Procedure stipulates that court decisions may not be based on evidence which is, directly or indirectly, by itself or in the manner of obtaining it, contrary to the Constitution, this Code, other law or generally accepted rules of international law and ratified international treaties, except in proceedings conducted for the purpose of obtaining such evidence. Illegal evidence cannot be used in criminal proceedings and is therefore separated from the case file. If the verdict is based on illegal evidence, it can be challenged in the appeal against the verdict, but also in the request for protection of legality. The subject of the paper is the analysis of the recent case law of the Supreme Court of Cassation (in the period from January 1, 2019 to December 31, 2020) regarding the requests for protection of legality stated in connection with illegal evidence.
Keywords: criminal proceedings, illegal evidence, Supreme Court of Cassation